Analisis Bioetika Islam terhadap Non-Invasive Prenatal Testing (NIPT) dan Pengambilan Keputusan Medis pada Kasus Anomali Janin: A Review - Gani Putri Aryanto (Himmah: Jurnal Kajian Islam Kontemporer, 2025)
Non-Invasive Prenatal Testing (NIPT) is a widely used prenatal screening method that enables early detection of fetal chromosomal abnormalities with minimal risk to both mother and fetus. Despite its clinical advantages, the increasing use of NIPT raises ethical concerns, particularly related to medical decision-making when fetal anomalies are identified. This article aims to review the application of NIPT and analyze ethical issues arising from prenatal decision-making through the perspective of Islamic bioethics. This study employed a narrative review method by analyzing national and international peer-reviewed journal articles published within the last five years, focusing on NIPT, ethical dilemmas, fetal anomaly management, and Islamic bioethical principles. The findings indicate that NIPT is clinically effective and ethically acceptable as a screening tool; however, challenges remain regarding informed consent, routinization of testing, reproductive autonomy, and the potential influence of screening results on decisions related to pregnancy continuation. From the perspective of Islamic bioethics, medical decision-making following NIPT should be guided by maqāṣid al-sharī‘ah, particularly the protection of life (ḥifẓ al-nafs), consideration of benefit and harm, and respect for human dignity. In conclusion, integrating Islamic bioethical values into prenatal care is essential to ensure ethical, responsible, and culturally sensitive use of NIPT in clinical practice. Keywords: Non-Invasive Prenatal Testing (NIPT), Islamic Bioethics, Fetal Anomalies, Medical Decision-Making, Prenatal Ethics